PENGARUH BUDAYA TERHADAP KETAKTERJEMAHAN ISTILAH-ISTILAH DALAM BAHASA JAWA - - Sukirmiadi (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2010)
Language is part of culture. Meanwhile there are many kinds of different cultures in the world because every country has its own culture. Even our country Indonesia has hundreds of cultures which are different between one and another, so that the language used varies also. MoreovThose er, every culture has its own peculiarity that is not owned by another culture. This fact that may cause so many specific words, terms, and other unique cultural events are created. This unique cultural product makes other people fom different cultures difficult to find the equivalences in their cultures and languages. Even those specific terms cannot be translated translated into other languages, especially English. Those unique cultural products include: 1) kinds of traditional foods (nagasari, thiwul, kethoprak, sega liwet); 2) agricultural tools (pacul, jompong, ani ani); 3) agricultural activity (ndhaut, matun, derep, ngasak); 4) kitchen utensils (siwur, keren, anglo, kukusan); 5) names of small plants (garut, ganyong, uwi); 6) music and art (saron, gender, kenong); 7) javanese songs (megatruh, sinom, pocong, slendro pelog); 8) names of dances (gambir anom, gambyong, klono bagus); 9) serving tools (takir, tumpeng, golong, sudhi); 10) clothes (kemben, jarik, blankon); 11) names of flower ( ketheker, karok, mayang); 12) names of leaves (sinom, blarak, jlegor); 13) ceremonies (sepasaran, midodareni, nyadranan, tingkepan, nyewu); and many others. It is very difficult to find the equivalences of those cultural products, or even they cannot be translated into other languages at all, especially in English. If this happens, the translator has just to write them in the source language by providing the specific notes or explaination about the meaning of those words according to the texts in a target language.